The noisy book - Soledad (Wellington, N.Z. : Gecko Press, 2012)
Presents a variety of sounds from animals and vehicles to babies and instruments.
Reprint. Originally published: 2010.
Preschool
Keywords: Sounds -- Juvenile literature; Animal sounds -- Juvenile literature; Sound; Animal sounds